Investigation of Cloud Computing Systems in Terms of Turkey and International Legislation - Dogan, Sengul; Yasar, Mehmet Fatih; Akbal, Erhan; Tuncer, Turker (Ieee, 2018)
Cloud computing is the name given to internet based information systems that are used and shared by users when necessary. The basic purpose of cloud computing is to provide sharing of resources without service infrastructure. Ensuring the security and integrity of these shared resources depend on the country's legislation. This study focuses on cloud computing systems. At the same time, cloud computing in our country and international legislation structure is presented problems and solution suggestions from different angles.
26th IEEE Signal Processing and Communications Applications Conference (SIU) -- MAY 02-05, 2018 -- Izmir, TURKEY
Keywords: Cloud computing; information systems; legal process